2016
DOI: 10.1007/s10157-016-1345-x
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive kidney transplantation: a propensity score matched cohort study

Abstract: PKT was associated with neither improvement of post-transplant renal function nor a lower rate of common post-transplant complications than non-PKT among patients with end-stage renal disease who underwent living KT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The JACK is an ongoing multicentre, observational cohort study conducted in Japan. The objectives and protocol of the JACK have been described in more detail previously 8 16 17. The participants were patients who underwent KT at Tokyo Women’s Medical University and visited the outpatient Yochomachi Clinic for follow-up assessments.…”
Section: Methodsmentioning
confidence: 99%
“…The JACK is an ongoing multicentre, observational cohort study conducted in Japan. The objectives and protocol of the JACK have been described in more detail previously 8 16 17. The participants were patients who underwent KT at Tokyo Women’s Medical University and visited the outpatient Yochomachi Clinic for follow-up assessments.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a physician has to be able to recommend an optimal time of transplantation when a patient with end-stage renal disease considers LDKT in order to minimize the length of dialysis duration for favorable long-term outcomes. Although Okumi et al [2] compared the clinical outcomes of PKT with those of non-PKT in a propensity-score-matched cohort, they only revealed that PKT was not associated with either improvement of post-transplant renal function or with a lower rate of common post-transplant complications compared with non-PTK. In the propensity-score-matched cohort of this study, however, it was evident that recipients with a short pretransplant dialysis duration had similar long-term outcomes to those who had PKT, whereas they had superior results to those with a long pretransplant dialysis duration in terms of mortality, graft survival, and BPAR.…”
Section: Discussionmentioning
confidence: 99%
“…KT candidates are considered to have a high prevalence of periodontal disease due to the status of end-stage of renal insufficiency, which is called stage-five CKD. There has been a recent increase in the number of preemptive kidney transplantation (PEKT) procedures, which are defined as transplant before initiation of maintenance dialysis therapy, for the avoidance of complication by dialysis therapy [80]. PEKT is often performed at the progression of renal deterioration in the pre-dialysis stage.…”
Section: Periodontal Disease and Kidney Transplantationmentioning
confidence: 99%